Dampak Promosi Online Terhadap Impulse Buying Online Produk Butik Sabrina Nganjuk - Lilis Sugi Rahayu Ningsih; Lik Anah; Rohmad Prio Santoso (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
This study supported manufacturers to meet the needs of consumers for online shopping through online promotions, concise services that contain full features of various e-commerce packages according to the advantages and values ​​of the company, making the consumers easier to purchase decisions and there were impulse buying online for products made by consumers. The aim of this study was to determine the impact of online promotions on online impulse buying of products at the Butik Sabrina in Nganjuk. This study used qualitative analysis of case studies using 80 respondents and 5 informants as samples. This study reveals that the impact of online promotion accompanied by an online shopping system on every online media promotion at Butik Sabrina, especially the consumers in making purchasing decisions has increased so that online product impulse buying occurs. The process of impulse buying online for Butik Sabrina products were as follow, online promotions are carried out by adjusting events, using live streaming social media and e-commerce to build relationships with consumers, and copy writing on social media and e-commerce to convince consumers